2005
DOI: 10.1007/s00122-005-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield responses to moisture regimes in a rice population: association among traits and genetic markers

Abstract: Drought is a major constraint to rice (Oryza sativa L.) production in rainfed and poorly irrigated environments. Identifying genomic regions influencing the response of yield and its components to water deficits will aid our understanding of the genetic mechanism of drought tolerance (DT) of rice and the development of DT varieties. Grain yield (GY) and its components of a recombinant inbred population developed from a lowland rice and an upland rice were investigated under different water levels in 2003 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 24 publications
8
66
2
2
Order By: Relevance
“…In the present study significant correlation was observed among the traits i.e., panicle length, number of chaff per panicle and spikelet fertility resulting in clustering of their QTLs on chromosome 6 in the same marker interval of RM253-RM30. Clustering of QTLs were also reported earlier in rice Zou et al, 2005) indicating tight linkage of different polygenes could be the possible reasons for the congruence of several QTLs. Another reason for the coincidence of QTLs is that character correlation may be attributed to the effect of pleiotropy or even very close linkage of genes (Lin et al, 1996).…”
Section: Clustering Of Qtlssupporting
confidence: 76%
“…In the present study significant correlation was observed among the traits i.e., panicle length, number of chaff per panicle and spikelet fertility resulting in clustering of their QTLs on chromosome 6 in the same marker interval of RM253-RM30. Clustering of QTLs were also reported earlier in rice Zou et al, 2005) indicating tight linkage of different polygenes could be the possible reasons for the congruence of several QTLs. Another reason for the coincidence of QTLs is that character correlation may be attributed to the effect of pleiotropy or even very close linkage of genes (Lin et al, 1996).…”
Section: Clustering Of Qtlssupporting
confidence: 76%
“…In this region, where SPIKE was identified, several QTLs for TSN have been detected, among which the alleles from japonica or tropical japonica cultivars increased TSN (30)(31)(32)(33)(34)(35)(36)(37)(38). Hitherto, no gene for TSN or grain yield in this cluster has been isolated (39).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, we detected drought-tolerant quantitative trait loci (QTL) in an RIL population from a cross of the Zhenshan97 and IRAT109 rice strains [86,87]. It was found that positive alleles for the majority of loci came from IRAT109.…”
Section: Global Analysis Of Drought Tolerance In Ricementioning
confidence: 90%
“…These stains are also used in several countries as a high-yielding and drought-resistant cultivar. IRAT109 is widely used as parental line in rice breeding programs and in the development of diverse genetic populations, such as the recombinant inbred line (RIL) or backcross inbred line (BIL) from crosses of Zhenshan97/IRAT109, IRAT109/Yuefu, and Akihikari/IRAT109 [86][87][88][89]. In our group, a comprehensive research platform was set up to conduct long-term research on rice drought resistance.…”
Section: Global Analysis Of Drought Tolerance In Ricementioning
confidence: 99%
See 1 more Smart Citation